Exploring the factors affecting employee motivation to be innovative on product development: A case study for Woolworths South Africa - Truter, Tessa (Marketing, 2022)
The global business industry is greatly affected by revolutionised human knowledge that requires a continued understanding of human preferences, needs and wants. Motivation to innovate must be understood when marketers aim for business success. Business success is seen in customer satisfaction and employee performance. The starting point for success is the miraculous ideas of employees. These ideas can be anything from the creation of a product or service to the execution of that product or service. Exploring the factors affecting the motivation to innovate on product development may lead marketers to business success by increased profitability, a bigger customer base, and retaining motivated skilled employees with the ability to innovate. This research is based on the South African multinational retailer Woolworths, with the focus on food and design packaging. A qualitative research approach was followed where data was collected from 11 participants using semi-structured individual face-to-face in-depth interviews and structured questionnaires. This study followed a manual thematic approach in an inductive manner. The needs of the participants in this study were categorised into three sections: Need for power, need for achievement and need for affiliation. This study also introduced McClelland's extended needs, and the motive for self-expression stood out among the cohort, confirming their creative skills. With the aid of individual components, domain-relevant skills, intrinsic task motivation and creativity stimulants, the study was able to link the presence of creativity to motivation and innovation. It confirmed that once the creativity intersection combines with organisational components there is a motivational synergy that produces innovation. The results of the study further indicated that internal motivation factors had a greater impact than external factors. As per organisational components, business values were shown to have an influence on the development of a product design. Legislation policies were deemed beneficial to forced creative thinking, yet it was also regarded as a limitation that can be improved through creative flexibility. Other factors that emerged were organisational socialisation, aligned stakeholder communication, sufficient market research, and respecting the emergence of seasonal trends. Future research should explore ways of improving organisational components that act as external influences on individual creative thinking. Moreover, future research should explore how effective training can help stakeholders learn and acquire the rights needs together with the continuous support from the business.